Maximum impact heights of currently used mouthguards in field hockey. Issue 4 (13th January 2020) - van Vliet, Kirsten E.; Kleverlaan, Cees J.; Lobbezoo, Frank; de Lange, Jan; van Wijk, Arjen J.
Abstract: Background/Aim: The effectiveness of mouthguards used in field hockey is unknown. The aim of this study was to compare the maximum impact heights between currently used mouthguards in field hockey to prevent dental injury. Methods: Four boil‐and‐bite mouthguards (Dita, Shock Doctor, SISU, and Stag) and one custom‐made mouthguard (Elysee) were tested for maximum impact height. A hockey ball was released in a tube from increasing heights onto plaster and polymethylmethacrylate (PMMA) dental models. Models were tested without mouthguard as a control. The experiment was repeated 10 times per mouthguard and for the control on each dental model. The maximum impact height for when the dental model broke was used to calculate the speed. The mouthguards and controls were compared. Results: The maximum impact heights (median [25%‐75%] in meters) onto plaster dental models were as follows: control 0.23 (0.15‐0.25), Dita 0.35 (0.30‐0.35), Elysee 0.45 (0.34‐0.50), Shock Doctor 0.68 (0.60‐0.74), SISU 0.23 (0.20‐0.26), and Stag 0.35 (0.35‐0.46). The maximum impact height for Shock Doctor was significantly higher than all other mouthguards and the control (all P  < .05). The maximum impact heights onto PMMA dental models were as follows: control 2.00 (1.30‐2.50), Dita 3.80 (2.65‐6.95), Elysee 3.30 (2.30‐4.20), Shock Doctor 6.20 (2.80‐8.10), SISU 2.60 (1.90‐3.15), and Stag 3.90 (1.25‐5.15). The maximum impact height for Shock Doctor was significantly higher than for SISU, Stag, and the control (all P  < .05), but did not differ significantly from Dita ( P  = .43) and Elysee ( P  = .12). Conclusion: Shock Doctor had the highest maximum impact height compared to the other mouthguards and appears to be the most effective mouthguard tested in this study.